The regional impact of discriminatory trade liberalization on Colombian agriculture (2009)
This study provides an assessment of the potential impact of trade liberalization on the regional structure of Colombian agriculture. For this, a two-step methodology is implemented. First, the effects of discriminatory trade liberalization are estimated by means of a multi-region general equilibrium model. Second, relevant price and quantity changes are transmitted to a simple transportation model that simulates the likely changes that trade liberalization will bring upon the spatial structure of agriculture. Results indicate that changes in the spatial structure of agricultural production in Colombia are not negligible and are instrumental for policy design on several fronts. © 2009 MCRSA.